Perception of innovation in Spain - Covadonga Gijón; Irene Albarrán Lozano; José Manuel Molina (International Telecommunications Society (ITS), 2021)
The present paper analyses the perception of innovation of individuals in Spain and the factors associated with it. Data from 2015 and 2018 about individuals from the Spanish surveys are used. The data include several measures of innovation perception, gender, age, educational level, and other socioeconomic and technical variables. The aim of this paper is to determine the perception of innovation, in its different aspects, of Spanish people. To this end, several ordered logit models have been developed to determine how much the socio-demographic characteristics and other aspects of innovation affect the perception of innovation. Results indicate that people have a better perception of innovation if they are training in innovation or have good Information and Communication Technology skills. Among the main results, there is evidence of a gender gap in the perception of innovation, as well as differences according to digital skills.
Keywords: C21; C25; D12; D83; J24; L63; L86; L96; M15; 330; perception; innovation; survey data; ordered logit